Interpreting Metaphor In Sidney Mohedeâ€™s Song Lyrics - Sumigar, F B; Maru, M G; Tuerah, I J C (Journal of Educational Method and Technology, 2019)
This research aimed at describing the metaphors used by the Mohede in the eight songs he wrote. As a qualitative research, this study rellied the data upon the lyrics of the chosen songs. The analysis applies theory of Lakoff and Johnson which divided metaphors into three types namely structural metaphor, orientational metaphor, and ontological metaphor. The analysis followed the steps of Bogdan and Biklen as follows identification, categorization, explanation, and interpretations of the findings. The result showed that the songs confirmed the existence the types of the metaphors such as structural metaphor, orientational metaphor and ontological metaphor. These findings implies a pivotal contribution of figurative speech particularly metaphor in communicating the meaning of a song. Thus, this study foreshadows a further research for comprehending the relationship of metaphor to song lyrics for both linguistic and literary context.Â Keywords: mathematical ability; students; Problem-Based Learning.